1989
DOI: 10.1107/s0021889889008289
|View full text |Cite
|
Sign up to set email alerts
|

X-ray study of CuGa x In1−x Se2 solid solutions

Abstract: The semiconducting compound CuGax I n~_xSe2 crystallizes in the chalcopyrite structure (space group

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…This shifts due to Ga homogenization after the 2nd step and the peak position 2h ¼ 26.82 (8 incident angle) corresponds to Ga/(In þ Ga) ¼ 0.19 when considering Vegard's law and the JCPDS database. 23,25,26 After the 3rd step, a broad second peak at 2h ¼ 27.70 is observed only for the scan with 0.5 incident angle and this is attributed to S diffusion at the front of the film.…”
Section: Resultsmentioning
confidence: 99%
“…This shifts due to Ga homogenization after the 2nd step and the peak position 2h ¼ 26.82 (8 incident angle) corresponds to Ga/(In þ Ga) ¼ 0.19 when considering Vegard's law and the JCPDS database. 23,25,26 After the 3rd step, a broad second peak at 2h ¼ 27.70 is observed only for the scan with 0.5 incident angle and this is attributed to S diffusion at the front of the film.…”
Section: Resultsmentioning
confidence: 99%
“…1). These compounds crystallize in the expected chalcopyrite structure (space-group I-42d), usually used to describe these compounds [8,10]. Cu-poor compounds #4, #5, #6 are also located on a line corresponding to Cu/(In + Ga) = 0.71 (Fig.…”
Section: Structural Reinvestigationmentioning
confidence: 99%
“…Although the CIGSe compounds have been known for a long time, literature is very poor about crystal structure studies [8][9][10][11] especially by single crystal X-ray diffraction technique. In a previous study [12] we have shown that the chalcopyrite structure is no longer valid for the description of Cu-poor and high Ga-content CIGSe compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The expected shift in the CIS (112) peak for the selenized Cu x' In y' B z' film as a result of substituting the smaller boron atom for the indium is not apparent and any small shift may be more consistent with mixed CIS and Cu 1.8 Se phases [8][9][10]. The XRD spectra for the selenized precursors are seen in figure 2.…”
Section: Resultsmentioning
confidence: 99%